Effect of Morchella esculenta polysaccharides on the rectal microbiota of mice challenged with lipopolysaccharides - Zhang, Yingjun; Qiu, Reng; Zhang, Zhifeng; Almutairi, Mikhlid H.; Nawaz, Shah; Dong, Shiqi (Frontiers in Veterinary Science, 2024)
IntroductionIntestinal dysfunction poses a severe problem by preventing the digestion and absorption of nutrients. The gut, being the most vital organ for these processes, plays a crucial role in ensuring our body receives the nutrients it needs. We explored the mitigating effect of Morchella esculenta polysaccharides (MEP) on intestinal injury induced by lipopolysaccharides (LPS) through the modulation of intestinal flora.MethodsFor this purpose, Kunming mice (KM) were divided into three groups, namely, PC, PM, and PY. Group PY was treated with MEP, while groups PM and PY were induced with LPS.ResultsThe results showed that weight loss in the PM group was significantly greater than that in the PY group (P < 0.05), and the organ indexes of the lung and spleen in the PM group were significantly higher than those in the PC (P < 0.01) and PY (P < 0.05) groups. LPS caused severe injuries in KM mice in the PM group, characterized by broken villi. However, MEP treatment could alleviate this damage in the PY group, resulting in relatively intact villi. The serum analysis showed that tumor necrosis factor alpha (TNF-ɑ) (P < 0.01), interleukin 6 (IL-6) (P < 0.01), and 3,4-methylenedioxyamphetamine (MDA) (P < 0.05) levels were significantly higher in the PM group, while IL-10 (P < 0.001), superoxide dismutase (SOD) (P < 0.01) and glutathione peroxidase (GSH-Px) (P < 0.01) were significantly lower in that group. Interestingly, supplementation with MEP could lower the levels of TNF-ɑ, IL-10, IL-6, MDA while increasing the levels of superoxide dismutase (SOD) (P < 0.01) and GSH-Px. The gut microbiota analysis yielded 630,323 raw reads and 554,062 clean reads, identifying 3,390 amplicon sequencing variants (ASVs). One phylum and five genera were notably different among animal groups, including Escherichia_Shigella, Limosilactobacillus, unclassified_Geminicoccaceae, unclassified_Rhodobacteraceae, and Parabacteroides (P. distasonis).DiscussionIn conclusion, we found that MEP could mitigate the intestinal damage caused by LPS by modulating the inflammatory response, oxidative resistance, and intestinal flora of KM mice. Our results may provide insights into novel treatment options for intestine-related diseases.